2013
DOI: 10.5231/psy.writ.2013.1611
|View full text |Cite
|
Sign up to set email alerts
|

Funcionamiento cognitivo en personas mayores e influencia de variables socioeducativas - Resultados del Estudio ELES

Abstract: El funcionamiento cognitivo experimenta cambios en las personas mayores. El grado de declive no es el mismo en todas las funciones cognitivas y otras variables, como el nivel educativo o el desempeño profesional a lo largo del ciclo vital, pueden hacer que dicho declive sea más lento. El objetivo del presente estudio es el de conocer el patrón de rendimiento cognitivo de las personas mayores de 50 años, teniendo en cuenta la influencia del nivel educativo y de la profesión. Los datos de esta investigación prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
2
2
0
1
Order By: Relevance
“…Regarding the first aim of this study, we establish gender-related differences in total MoCA test performance, as well as a negative association between the total MoCA test performance with age and severity of depressive symptoms, and a positive relationship with years of schooling. Our findings are in line with other works that report differences based on gender [ 13 , 14 ] age [ 12 ], depression symptoms [ 17 , 18 , 20 ], and years of schooling [ 26 , 27 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Regarding the first aim of this study, we establish gender-related differences in total MoCA test performance, as well as a negative association between the total MoCA test performance with age and severity of depressive symptoms, and a positive relationship with years of schooling. Our findings are in line with other works that report differences based on gender [ 13 , 14 ] age [ 12 ], depression symptoms [ 17 , 18 , 20 ], and years of schooling [ 26 , 27 ].…”
Section: Discussionsupporting
confidence: 93%
“…Cognitive deterioration is not general and homogeneous among the affected individuals; in fact, it has been shown that people with higher level of education show better cognitive performance at old age, which confirms the effect of the variables associated with cognitive reserve in the maintenance of cognitive functioning in adulthood [ 26 , 27 ]. Similarly, education has been described to be a protective element against cognitive deterioration, associated with the amount of cognitive loss required for the appearance of symptoms [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…The levels of variance explained by these variables in the current study (MoCA Basic = 31.8% and MoCA Full = 33.8%) were somewhat lower than those found by Freitas et al [28] with a Portuguese population, who found age and education explained 49% of the variance in MoCA Full scores. Results from this study are also consistent with several studies indicating that the total MoCA score consistently increases with educational level and decreases with advancing age [23,36,[49][50][51][52]. Rossetti et al [32] found, in a North American population, that performance decreases to a lesser extent with age in those participants with 12 years of education, and more in those with less education.…”
Section: Discussionsupporting
confidence: 91%
“…The relationship between educational level and cognitive performance may be explained in part by a higher prevalence of healthy behaviors in more educated people, such as better nutrition, greater physical and mental activity, greater autonomy at the work level, etc. [31, 51, 52]. If true, this relationship could indicate that the mentioned variables are protective factors for cognitive impairment, and therefore result in better performance in cognitive assessment instruments in adults.…”
Section: Discussionmentioning
confidence: 98%
“…Al analizar los datos según la edad, se observó en ambos grupos que las puntuaciones de todas las áreas cognitivas experimentaban un descenso de forma significativa conforme aumentaba la edad, mostrando estos resultados consistencia con los hallazgos de otros estudios 22 . Con respecto al sexo hallamos asociación con el DC dentro de la institución, con mayor prevalencia en mujeres, no existiendo grandes diferencias de sexo fuera de la institución.…”
Section: Discussionunclassified